PERENCANAAN JARINGAN 5G NR PADA FREKUENSI 28 GHz BERBASIS SOFTWARE ATOLL DI KOTA MALANG, JAWA TIMUR - Rifaldy Yuhendri; Sigit Kusmaryanto; Gaguk Asmungi (Jurnal Mahasiswa TEUB, 2022)
Telecommunications network technology has entered the fifth generation or often called 5G NR. The availability of 5G NR network services is expected to be a solution to improve the quality of telecommunication networks in Malang City. The research in this thesis plans a 5G NR network at a frequency of 28 GHz and a bandwidth of 100 MHz, by analyzing the needs of gNodeB in Malang City and user projections from 2020 to 2025. The methods of analyzing the needs of gNodeB discussed are coverage dimensioning and capacity dimensioning. From the analysis day, the predicted number of people using the 5G NR network in 2025 is 378,052 people. The number of gNodeB needed is based on the calculation of coverage dimensioning as much as 921 gNodeB and Capacity dimensioning of 74 gNodeB. The planning results are simulated on the Atoll software. Where obtained the placement of 74 gNodeB in the Malang City area has been able to serve users. Keywords –5G, coverage dimensioning, capaity dimensioning, 28 GHz, ATOLL.